Sex differences in patients with cardiogenic shock. (24th March 2021) - Yan, Isabell; Schrage, Benedikt; Weimann, Jessica; Dabboura, Salim; Hilal, Rafel; Beer, Benedikt N.; Becher, Peter Moritz; Seiffert, Moritz; Magnussen, Christina; B. Schnabel, Renate; Kirchhof, Paulus; Blankenberg, Stefan; et al.
Abstract: Aims: Differences between female and male patients in clinical presentation, causes and treatment of cardiogenic shock (CS) are poorly understood. We aimed to investigate sex differences in presentation with and treatment of CS. Methods and results: We analysed data of 978 patients presenting with CS to a tertiary care hospital between October 2009 and October 2017. Multivariable adjusted logistic/Cox regression models were fitted to investigate the association between sex and clinical presentation, use of treatments and 30 day mortality. Median age was 70 years (interquartile range 58–79 years), and 295 (30.2%) patients were female. After adjustment for multiple relevant confounders, female patients were more likely to be older [odds ratio (OR) 1.21, 95% confidence interval (CI) 1.02–1.42, P = 0.027], but other relevant presentation characteristics did not differ between both sexes. Despite the similar presentation, female patients were less likely to be treated with percutaneous left ventricular assist devices (OR 0.78, 95% CI 0.64–0.94, P = 0.010), but more likely to be treated with catecholamines (OR 1.21, 95% CI 1.02–1.44, P = 0.033) or vasopressors (OR 1.26, 95% CI 1.05–1.50, P = 0.012). A 30 day mortality risk in female patients was as high as in male patients (hazard ratio 1.08, 95% CI 1.00–1.18, P = 0.091). Conclusions: In this large, contemporary cohort, clinical presentation was comparable in female and male patients, and both sexes were associated with a comparably high mortality risk. Nevertheless, female patients received different treatment for CS and were most importantly less likely to be treated with percutaneous left ventricular assist devices.